Herbicide selectivity for peach palm (Research, Society and Development, 2025)
The peach palm (Bactris gasipaes) is a palm tree native to the Amazon and its fruits are consumed by amazonian people and are a source of income for extractivists and smallholders. In addition to the traditional use, the peach palm has been exploited for sustainable production of heart of palm due to the tillering of the plants, and the cultivated area has expanded to meet the demand of the heart of palm agroindustry. Like any crop, the peach palm suffers negative interference from weeds that cause reduced plant growth and yield and quality of the heart of palm. Weed control with herbicides is an alternative to manual control, as it is less labor-intensive, has lower operational costs, and is highly effective during the rainy season. Thus, the objective of this study was to evaluate the selectivity of the herbicides 2,4-D dimethylamine (670, 1005, 1340 and 1675 g), diuron (750, 1250, 1750 and 2250 g), metribuzin (240, 480, 720, 960 g) and fenoxaprop (55, 82.5, 110 and 137.5 g). The experiment was conducted in nursery conditions in pots with peach palm seedlings at the stage growth of four fully expanded leaves. 2,4-D, diuron and metribuzin were applied under the canopy of the seedlings and fenoxaprop on the leaves. All herbicides at all doses were selective for peach palm.